Elucidating the effects of DNA modification on transcription - Yavorska, O (2021)
DNA modifications play important roles in genome function of vertebrates. 5-methylcytosine (mC) has been extensively studied over the last 50 years as the most common covalent DNA modification, present at roughly 70% of CpGs in the human genome. At promoters it is mostly associated with silencing of genes. An oxidative product of mC, 5-hydroxymethylcytosine (hmC), was found to be common in brain cells in 2007, and studies have attempted to elucidate the function of this stable modification ever since. Although gene silencing through promoter-proximal DNA methylation has been extensively described, the correlation between abundance of mC and hmC in gene bodies and expression is less well understood. In this study we investigate the relationship between DNA modifications, active transcription, and gene expression. Using a system of global mC and hmC perturbation, we contrast the effects of mC loss (mC to C) and hmC gain (mC to hmC) on different transcription stages: initiation (sense and antisense), pausing, and elongation. The induced changes in transcription are modest but proportional to the changes in DNA modifications, and observations are consistent across multiple analyses. mC loss is more disruptive to actively transcribing RNA polymerase (RNAP) occupancy and gene expression compared to hmC gain. The effects of hmC gain are modest, but both mC loss and hmC gain result in upregulated initiation (both canonical and spurious), elongation, pause-release, and gene expression. Overall we observe quantitative differences between loss of mC and gain oh hmC suggesting that hmC may have a role beyond intermediate of demethylation.